Insight into the Mechanochemical Synthesis and Structural Evolution of Hybrid Organic–Inorganic Guanidinium Lead(II) Iodides. Issue 67 (15th November 2018) - Wilke, Manuel; Casati, Nicola
Abstract: The in situ investigations of the mechanochemical synthesis of four hybrid organic–inorganic lead(II) iodides with the formula (C(NH2 )3 ) n PbI2+ n ( n= 1, 2, 3, and4 ) are presented. Synchrotron X‐ray diffraction data show that the four guanidinium lead(II) iodides easily convert into each other. Although the end product is dictated by the initial stoichiometry, complex pathways were found with different behaviors of the compounds in terms of nucleation, growth, and intermediate formation. This appears to be linked to the respective structural features of the different compounds, especially the connectivity of the inorganic framework and the strength of ionic interactions. High‐temperature studies were conducted on compounds1, 3, and4 to reveal the new phases1‐II, 3‐II, and3‐III . Unknown structures were solved from single‐crystal analysis and powder X‐ray diffraction. Abstract : Mix it up : Mechanochemistry has been used for the easy and fast synthesis of hybrid organic–inorganic guanidinium lead(II) iodides of different dimensionality. Although the end product is dictated by the initial stoichiometry, complex pathways were found with different behaviors of the compounds in terms of nucleation, growth, and intermediate formation.